Selection of approach and fixation in the treatment of - QI Xin; LIU Jian-guo; GONG Yu-bao; YANG Chen; LI Shu-qiang; FENG Wei (Chinese Journal of Traumatology, 2010)
Unlike the common distal humeral fracture in children, the prevalence of fractures at this site is not high in adults and accounts for only 2% of all fractures.Moreover, intraarticular fractures, especially the type C fracture, are rare and usually caused by high energy injury. After fractures occur, there are problems of disconnection between the condyles and diaphysis, and of disruption between the medial and lateral condyles. The two condyle fragments rotate along their own axes and the trochlea is usually intact. All these factors create difficulties for reduction and fixation. The currently employed surgical approaches are usually not able to provide enough exposure, and sufficient stability can not be achieved by internal fixation to allow early functional exercises. There are still difficulties in the management of intra-articular fractures of the distal humerus in adults.1, 2 Our objective is to study the surgical treatment for distal humeral fractures in adults by patients’ follow-up.